Impact of prenatal hypoxia on the development and behavior of the rat offspring - Piešová, M; Koprdová, M; Ujházy, E; Kršková, L; Olexová, L; Morová, M; Senko, T; Mach, M (Physiological research, 2020)
The healthy development of the fetus depends on the exact course of pregnancy and delivery. Therefore, prenatal hypoxia remains between the greatest threats to the developing fetus. Our study aimed to assess the impact of prenatal hypoxia on postnatal development and behavior of the rats, whose mothers were exposed to hypoxia (10.5 % O2) during a critical period of brain development on GD20 for 12 h. This prenatal insult resulted in a delay of sensorimotor development of hypoxic pups compared to the control group. Hypoxic pups also had lowered postnatal weight which in males persisted up to adulthood. In adulthood, hypoxic males showed anxiety-like behavior in the OF, higher sucrose preference, and lower levels of grimace scale (reflecting the degree of negative emotions) in the immobilization chamber compared to the control group. Moreover, hypoxic animals showed hyperactivity in EPM and LD tests, and hypoxic females had reduced sociability compared to the control group. In conclusion, our results indicate a possible relationship between prenatal hypoxia and changes in sociability, activity, and impaired emotion regulation in ADHD, ASD, or anxiety disorders. The fact that changes in observed parameters are manifested mostly in males confirms that male sex is more sensitive to prenatal insults.
Keywords: Behavior, Animal; úleková reakce; hypoxie plodu; pohybová aktivita; senzorimotorický kortex; sociální interakce; Social Interaction; Sensorimotor Cortex; těhotenství; Fetal Hypoxia; sexuální faktory; Disease Models, Animal; Gestational Age; Rats, Wistar; mužské pohlaví; Maze Learning; věkové faktory; gestační stáří; Acid-Base Equilibrium; modely nemocí na zvířatech; ženské pohlaví; Reflex, Startle; zvířata; acidobazická rovnováha; Pregnancy; Sex Factors; zpožděný efekt prenatální expozice; chování zvířat; Age Factors; preference v jídle; potkani Wistar; Motor Activity; Food Preferences; Female; bludiště - učení; Prenatal Exposure Delayed Effects; Male; Animals